1987
DOI: 10.1111/j.1559-1816.1987.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Young Adolescent Cigarette Smoking: A Sixteen‐Month, Three‐Wave Longitudinal Study1

Abstract: Understanding the psychosocial factors that predict cigarette smoking onset in young people is of crucial importance for prevention efforts. The present study examined prospective psychosocial predictors of smoking in a three‐wave longitudinal data set. Similar in design to an earlier study by Chassin, Presson, Sherman, Corty, and Olshavsky (1984), the present study replicated their work, and extended it by (a) using composite predictors derived from exploratory factor analysis, (b) including prior behavior as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 27 publications
11
82
1
2
Order By: Relevance
“…Nonetheless, after controlling for confounding influences, parental disapproval on adolescent smoking was found to be not associated with smoking susceptibility (Table 3). These findings are contrary to those reported by other researchers (Collins et al, 1987;Sargent and Dalton 2001;Peimack et al, 2007;Kong et al, 2012;Page et al, 2012;Vazquez-Rodrigues et al, 2012). As early as in 1987, Collins et al surveyed 3,295 urban teenagers aged 12 to 13 years and found that social disapproval was one of the significant predictors of future smoking.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Nonetheless, after controlling for confounding influences, parental disapproval on adolescent smoking was found to be not associated with smoking susceptibility (Table 3). These findings are contrary to those reported by other researchers (Collins et al, 1987;Sargent and Dalton 2001;Peimack et al, 2007;Kong et al, 2012;Page et al, 2012;Vazquez-Rodrigues et al, 2012). As early as in 1987, Collins et al surveyed 3,295 urban teenagers aged 12 to 13 years and found that social disapproval was one of the significant predictors of future smoking.…”
Section: Discussionmentioning
confidence: 73%
“…It revealed that the stronger the perceived social or parental disapproval, the less likely they become susceptible to smoking (Collins et al, 1987;Peimack et al, 2007;Kong et al, 2012;Page et al, 2012). However, the univariate analysis demonstrated that only perceived parental disapproval exerted significant effect to reduced smoking susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, decades of school-based research on adolescents have repeatedly demonstrated that adolescents' perceptions of the norms and values of their peers are strongly associated with their risk-taking and antisocial behaviors. [13][14][15][16][17][18] It is important that we examine not only the rates of sexting, but that we understand how such behaviors are tied to adolescents' perceptions of the sexting behaviors of their peers or other persons whom they know.…”
Section: Resultsmentioning
confidence: 99%
“…Perceived smoking prevalence is known to have a strong influence on youth smoking initiation. 1,[43][44][45][46] The Massachusetts advertisements aimed to denormalize tobacco use by showing youths that smoking by their peers is not the norm. The f irst advertisement featured a crowd of youths mobilizing to "make smoking history in Massachusetts."…”
Section: Discussionmentioning
confidence: 99%